Mechanization in sugarcane production and other agricultural activities: an econometric analysis of employment and income - Diogo Ferraz; Fabíola Cristina Ribeiro de Oliveira; Daisy Aparecida do Nascimento Rebelatto; Andreas Pyka (Gestão & Produção, 2021)
Abstract: Several studies argue that agricultural mechanization has reduced employment and wages. However, there is a lack of studies analyzing employment and income over time, especially comparing the agricultural activities. Our major argument is the structural change in the employment - from un-skilled to skilled workers which has to be understood because of the overall decrease in the number of jobs. This study aims to analyze the labor market evolution in sugarcane farming and other agricultural activities, from 1992 to 2015. Using the National Household Sample Survey (PNAD/IBGE), we compared sugarcane and other Brazilian crops using econometrics techniques. We analyzed the Heckman's procedure and models with fixed effects panel data, controlling the unobservable characteristics of workers. Methodologically, our equations show convergence, since the Heckman procedure and pooled regression present similar estimates. We showed that fixed-effect regression captures the same trends of Ordinary Least Square (OLS) technique, using the Heckman method. Our main findings suggest that the wage of sugarcane workers is higher than wages in other crops, even after we control the observable and regional characteristics. This finding is important because the sugarcane sector has faced criticism regarding the low level of employment and income due to the mechanization process. Finally, we pointed out the decrease in unskilled jobs in sugarcane, which demands for policy intervention to improve the human capital in the sugarcane sector.